Gender differences in the language use of Malaysian teen bloggers - Zaini Amir,; Hazirah Abidin,; Saadiyah Darus,; Kemboja Ismail, (Penerbit UKM, 2012)
Past researches have shown that there is a difference in language use between males and females attributed by their roles and society’s stereotyping or perceptions. Fast changing technology has provided another means for young people to express themselves using language as a tool. This study investigates the differences in language use by female and male Malaysian teenage bloggers who use blogs as a diary to express their daily issues about life. The language used is informal and similar to spoken language. Using a qualitative approach, this study aims to examine gender differences observed in the language features used by male and female teenagers in their blogs. The findings show that there are differences between male and female bloggers in the frequencies of five language features which are ‘intensifiers’, ‘hedging’, ‘tag questions’, ‘empty adjectives’and ‘adverbs’. The results of the study show that differences in language use among teenage bloggers may largely be attributed to gender.